2014
DOI: 10.1371/journal.pone.0085419
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Is a Negative Cell Surface Marker for Pluripotent Stem Cell Identification during Human Fibroblast Reprogramming

Abstract: Induced pluripotent stem cells (iPSCs) are promising tools for disease research and cell therapy. One of the critical steps in establishing iPSC lines is the early identification of fully reprogrammed colonies among unreprogrammed fibroblasts and partially reprogrammed intermediates. Currently, colony morphology and pluripotent stem cell surface markers are used to identify iPSC colonies. Through additional clonal characterization, we show that these tools fail to distinguish partially reprogrammed intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…Some of these transcripts are Klf4, Ina, Nr0b1, and Lrrc2, which are known pluripotency factors critical for the maintenance of the stem state [23]. Interestingly, we also observed an increase in tsGlnCTG association with pro-differentiation transcripts such as Myl3, CD44, and Dkk3 [24][25][26] (Fig 4D 0 and Dataset EV5). While initially counter intuitive, upon closer examination of these transcripts, we noticed a significant association (P value < 0.05) with genes involved in skeletal, cardiovascular, and blood vessel development compared with neuronal lineage (Dataset EV6).…”
Section: Of 18mentioning
confidence: 59%
“…Some of these transcripts are Klf4, Ina, Nr0b1, and Lrrc2, which are known pluripotency factors critical for the maintenance of the stem state [23]. Interestingly, we also observed an increase in tsGlnCTG association with pro-differentiation transcripts such as Myl3, CD44, and Dkk3 [24][25][26] (Fig 4D 0 and Dataset EV5). While initially counter intuitive, upon closer examination of these transcripts, we noticed a significant association (P value < 0.05) with genes involved in skeletal, cardiovascular, and blood vessel development compared with neuronal lineage (Dataset EV6).…”
Section: Of 18mentioning
confidence: 59%
“…Some of these transcripts include Klf4, Ina, Nr0b1 and Lrrc2, which are known pluripotency markers critical for the maintenance of the stem state (Sharova et al, 2007). However, we also observed an increase in tsGlnCTG association with pro-differentiation transcripts like Myl3, CD44 and Dkk3 (Cohen-Haguenauer et al, 1989;Quintanilla et al, 2014;Wang et al, 2015) (Fig. 3B' and Table S3).…”
Section: Tsrnas Regulate Specific Targets Through Their Protein Intermentioning
confidence: 53%
“…CD44 is a cell membrane glycoprotein that mediates the cellular response to the cellular microenvironment and regulates growth, survival, differentiation, and motility (Loh et al, 2014). CD44 is a negative cell surface marker of pluripotent stem cell identification during human fibroblast reprogramming (Quintanilla Jr. et al, 2014) and regulates endothelial cell proliferation and apoptosis by modulating CD31 and VE-cadherin expression (Tsuneki and Madri, 2014). A previous study suggested that CD44 contributed to lenalidomide resistance in multiple myeloma (Bjorklund et al, 2014).…”
Section: Discussionmentioning
confidence: 99%